Strengthening the energy policy making process and sustainability outcomes in the OECD through policy design - Andrew Chapman; Benjamin McLellan; Tetsuo Tezuka (Administrative Sciences, 2016)
This study investigates the nature of the energy policy making process and policy priorities within the OECD in order to identify opportunities for improvement in these processes and to improve sustainability outcomes. The Qualitative Content Analysis methodology is used, investigating governance and energy policy making alongside energy policy goals and priorities within eight OECD nations. A congruous energy policy making process (policy cycle) is discovered across the assessed nations, including the responsible bodies for each stage of the policy cycle and the current energy policy priorities. A key weakness was identified as a disconnect between the early stages of the policy cycle, issue identification and policy tool formulation, and the latter stages of implementation and evaluation. This weakness has meant that the social aspects of sustainability goals have been less developed than environmental and economic aspects and a heavy burden has been placed on the evaluation phase, risking a break down in the policy cycle. An additional "policy design" stage is proposed including a sustainability evaluation process prior to decision making and implementation, in order to remedy these identified shortcomings.
Keywords: 350; energy; policy; policy cycle; OECD; sustainability